2016
DOI: 10.3141/2543-13
|View full text |Cite
|
Sign up to set email alerts
|

Tool to Assess Regional Public Transport Plans for Integrated Systems

Abstract: This study developed a tool that can be used by planners to assess the quality of their regional public transport plan and to produce a well-integrated system. The five attributes of integration—network integration, integrated timed transfer, integrated physical connection for transfers, information integration, and fare and ticketing integration—were adopted to develop a framework that illustrated the relationship between them. The tool was composed of the developed framework and a multicriterion decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As discussed earlier, more transport authorities are focusing on transforming their PT network into an integrated multi-modal system (Chowdhury et al, 2016). As these systems are reliant on transfers, it means that a typical route will require the user to spend more time outside vehicles compared to a direct route.…”
Section: Waiting Timementioning
confidence: 99%
“…As discussed earlier, more transport authorities are focusing on transforming their PT network into an integrated multi-modal system (Chowdhury et al, 2016). As these systems are reliant on transfers, it means that a typical route will require the user to spend more time outside vehicles compared to a direct route.…”
Section: Waiting Timementioning
confidence: 99%
“…Chowdhury et al summarized the willingness into 3 aspects, namely psychological, operational, and policy [4]. Starting with the psychological, Literature analyzing the general attitude of travelers towards PT use has shown that, although improvement in service quality is likely to increase ridership, the level of increase can be limited if travelers hold prejudices towards the image of PT and of becoming user [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chowdhury summarized the transfer willingness into 3 aspects, namely psychological, operational, and policy [4]. The influencing factors are classified according to their contribution to each aspect.…”
Section: Analysis Of Passengers' Mode Choicementioning
confidence: 99%
“…In this step, a search engine for connections needs to be selected according to input criteria [41]. Manual searching in timetables is the primary search method.…”
Section: Selecting Search Engines For Transport Connectionsmentioning
confidence: 99%
“…This study is also focused on time-based synchronization in transfer points, as discussed in transport related studies in publications as well [39][40][41][42][43][44], where the effects of travel times on cost savings in terms of commuting on public transport routes and passengers' behavior under regional conditions in Eastern Europe are sequentially being discussed. Support for individual transport mode connections to the railway network is examined in [45,46], and a variety of case studies to increase the share of railway transport within the limitations of existing railway network are addressed in [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%